Geocronologia Rb/Sr e K/Ar dos granitóides sintectônicos à Zona de Cisalhamento Transcorrente Dorsal de Canguçu na região de Encruzilhada do Sul (RS) - KOESTER, EDINEI; SOLIANI JUNIOR, ENIO; FERNANDES, LUIS ALBERTO D'ÁVILA; KRAEMER, GUSTAVO; TOMMASI, ANDRÉIA (Pesquisas em Geociências, 1997)
The result of seventeen whole-rock Rb/Sr and four K/Ar isotopic analyses of syntectonic granites to the Transcurrent Dorsal de Canguçu Shear Zone are reported in this paper. The early magmatism along that fault is represented by the Quiteria metagranite-granodiorite which crops out into three main bodies and presents an age of 672 ± 21 Ma (Ro = 0.716 ± 0.001). The late magmatism corresponds to the emplacement of peraluminous leucogranites of Cordilheira Granitic Suite comprising the older Arroio Francisquinho metamonzogranite yielding an age of 629 ± 23 Ma (Ro = 0.733 ± 0.001) and the younger Cordilheira metagranite with an age of 617 ± 48 Ma (Ro = 0.740 ± 0.006). Metamorphic episodes affecting these rocks are of low temperatures so that all these results can be interpreted as crystallization ages K/Ar ages about 590 Ma obtained for these rocks were interpreted as the reseting ages of this isotopic system, probably caused by intrusion of large volume of post-tectonic granitoids. A discussion of the implications of these ages for the understanding of the magmatism related with the evolution of the Dom Feliciano Belt during the Neoproterozoic, with emphasis in the role played by the syntranscurrent igneous intrusions is presented.